Isolation of Kerosene degrading bacteria from soli samples and determination of optimum growth conditions - Chowdhury, Mashiat Nawar (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2015.